A Literature Review on Factors Influencing Non-Adherence to Antiretroviral (ARV) Among People Living with HIV - Nila Imtihani; Menap Menap (Universitas Tribhuwana Tunggadewi, 2025)
Non-adherence to antiretroviral therapy (ART) among people living with HIV (PLHIV) remains a significant global challenge in the effort to control the HIV/AIDS epidemic. In Indonesia, although access to ART continues to expand, adherence rates remain below the optimal threshold, thereby compromising treatment effectiveness and increasing the risk of drug resistance and secondary transmission. This literature review aims to explore and categorize the factors contributing to ART non-adherence among adult PLHIV. A narrative literature review was conducted through systematic searches of four major databases: PubMed, ScienceDirect, Scopus, and SpringerLink. Articles were selected based on inclusion criteria such as publication year (2019–2025), relevance to ART adherence, and focus on adult PLHIV populations. Ten eligible articles were analyzed thematically to identify common barriers to adherence. The findings indicate that ART non-adherence is influenced by a combination of individual, social, and health system-related factors. Individual-level barriers include depression, anxiety, medication side effects, and lack of motivation. Social factors such as stigma, insufficient family or peer support, and cultural beliefs significantly hinder adherence. Meanwhile, health system barriers encompass unwelcoming services, inflexible schedules, lack of patient education, and complex administrative procedures. These results underscore the importance of a comprehensive, multidisciplinary approach involving psychosocial support, stigma reduction, community-based interventions, and health system reform. This review also recommends future empirical studies employing more rigorous methodologies and localized research that can inform the development of contextually and culturally appropriate interventions.